Predicting Air Traffic Controller Workload from Eye-Tracking Data with Machine Learning - Lemetti, Anastasia; Meyer, Lothar; Peukert, Maximilian; Polishchuk, Tatiana; Schmidt, Christiane; Alpfjord Wylde, Helene (Journal of Open Aviation Science, 2025)
In this paper, we examine the feasibility of assessing air traffic controller (ATCO) workload using non-intrusive eye-tracking measures and machine learning algorithms. A total of N = 18 ATCOs participated in simulator runs with tasks inducing three task-load levels: light, moderate, and heavy. Task load was modulated through traffic load and the associated increase in complexity. We collected eye-tracking data (statistical summaries of which serve as features) and obtained subjective workload assessments using self-reported Cooper-Harper Scale scores, which act as label variables. We evaluate the performance of eight classical machine learning models, with the k-nearest neighbors and support vector classifier models emerging as the most promising. To optimize performance, we apply feature selection techniques, focusing on these best-performing models. Feature selection via recursive feature elimination (RFE) based on permutation importance reduces the original 42 features while maintaining or improving performance. The outcomes yield promising results in workload-level estimation, achieving an F1 score of 0.870 for low/high workload prediction and an F1 score of 0.788 for predicting three different levels of workload. The RFE process identifies optimal feature sets ranging from 7 to 13 features for different tasks, with minimal impact on performance. A “knee point” is observed, representing the optimal balance between model performance and dimensionality. Adding more features beyond this point contributes little to performance improvement while increasing model complexity. These findings indicate that even a few features can be sufficient for accurate workload prediction. We show that head-movement features provide valuable information. Comparable performance is achieved using only ocular features, but this requires more features. Asymmetry in left and right eye metrics holds workload-related information but transforming them into averages and differences reduces performance. Retaining the original features separately is the most effective approach, incorporating their absolute differences may provide slight benefits in certain models.